Chalcogen OCF3 Isosteres Modulate Drug Properties without Introducing Inherent Liabilities. (21st August 2019) - Ghiazza, Clément; Billard, Thierry; Dickson, Callum; Tlili, Anis; Gampe, Christian M.
Abstract: The synthesis of SCF3 as well as SeCF3 isosteres of two OCF3 ‐containing drugs was achieved through visible light and copper‐catalyzed processes. Herein, we show that chalcogen replacement modulates physicochemical and ADME properties without introducing intrinsic liabilities. The SCF3 and SeCF3 groups are more lipophilic than their oxygen counterpart; however, microsomal stability is unchanged, indicating that these molecular changes may be beneficial for in vivo half‐life. Enabled by modern synthetic methods, we present the chalcogen‐CF3 groups as potential key players for future fluorinated pharmaceuticals. Abstract : Oxygen, Sulfur or Selenium? The replacement of OCF3 by SCF3 and SeCF3 analogues was undertaken for the synthesis of chalcogen OCF3 isosteres. The physicochemical and ADME properties can be modulated by the presence of sulfur or selenium, and it turns out that no intrinsic pharmacological liability was observed, paving the way to the design of new molecules containing SCF3 and SeCF3 .